PENGLIBATAN DALAM AKTIVITI BAGI MENGURANGKAN MASALAH TINGKAH LAKU HIPERAKTIF - Yusop Malie; Fatimah Az-Zahra; Nur Farhana Kamel; Nurulain Pusa; Ririn Yiichasiani; Sabariah Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
The purpose of this study was to investigate the behaviour problems of trainees in Community- Based Rehabilitation (CBR) related to hyperactive. This study involved a trainee named Fariz from one of the Community-Based Rehabilitation. Observation method was used in this study to be recorded for two weeks about the hyperactive behaviour shown. Various activities were held to find out how the impact of the trainee’s involvement in order to maintain his focus span. The finding of this study shows that there was a positive feedback regarding the less hyperactive behaviour shown by the trainee when given a role or work. This study also recommended other suggestions to reduce the hyperactive behaviors among children with learning disabilities.